2004
DOI: 10.1136/adc.2003.033100
|View full text |Cite
|
Sign up to set email alerts
|

Chest physiotherapy, gastro-oesophageal reflux, and arousal in infants with cystic fibrosis

Abstract: Background: Postural drainage chest physiotherapy in infants with cystic fibrosis (CF) exacerbates gastrooesophageal reflux (GOR) and may contribute to a more rapid deterioration in lung function. Aims: To compare standard postural drainage chest physiotherapy (SPT) and a modified physiotherapy regimen (MPT) without head-down tilt, with regard to GOR, arousal state, and cardiorespiratory function. Methods: Twenty infants with CF underwent 30 hour oesophageal pH monitoring, during which four chest physiotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
14

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 27 publications
1
34
1
14
Order By: Relevance
“…[27][28][29] No wonder that conventional CPT gives poor results and is poorly tolerated, with side effects such as esophageal reflux, tachypnea, tachycardia, hypoxemia, rib fracture, and severe central nervous system complications, especially in newborns. [30][31][32][33][34] The 2012 Cochrane review showed no significant benefit from conventional CPT on clinical score or hospital stay, and conventional CPT in acute viral bronchiolitis is no longer recommended. [35][36][37] In France, increased-exhalation technique has been widely used in various ways since the 1970s.…”
Section: Chest Physical Therapymentioning
confidence: 99%
“…[27][28][29] No wonder that conventional CPT gives poor results and is poorly tolerated, with side effects such as esophageal reflux, tachypnea, tachycardia, hypoxemia, rib fracture, and severe central nervous system complications, especially in newborns. [30][31][32][33][34] The 2012 Cochrane review showed no significant benefit from conventional CPT on clinical score or hospital stay, and conventional CPT in acute viral bronchiolitis is no longer recommended. [35][36][37] In France, increased-exhalation technique has been widely used in various ways since the 1970s.…”
Section: Chest Physical Therapymentioning
confidence: 99%
“…Reflux episodes, as measured with a pH probe reading of Ͻ 4, occurred most often during crying. 75 Button and colleagues reported no differences in heart rate or oxygen saturation during reflux episodes, 75 which illustrates what some call silent aspiration. pH probe monitoring cannot detect whether reflux contents reach the airways.…”
Section: Gastroesophageal Refluxmentioning
confidence: 99%
“…Modifying CPT by excluding head-down positions may decrease the number of reflux episodes. 75 During modified CPT, infants are more likely to remain calm. Keeping the infant calm can decrease intra-abdominal pressure produced by crying.…”
Section: Gastroesophageal Refluxmentioning
confidence: 99%
See 1 more Smart Citation
“…Cette dernière nécessite le recours à la kinésithérapie [4] dont certaines manoeuvres de désencombrement ont été associées au RGO même si les publications restent peu nombreuses [5][6][7][8]. Au vu de cette association possible, il est intéressant de s'assurer de l'innocuité des techniques de kinésithérapie chez ces patients.…”
Section: Introductionunclassified